Konsep Pendidikan Anak Usia Dini Perspektif Q.S Luqman Ayat 13-19 - Ibnu Imam Al Ayyubi; Ai Sri Masfuroh; Firda Noerzanah; Abdul Muhaemin; Niken Siti Nur Apriyanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This research aims for parents in particular to learn lessons from Luqman's story, namely regarding the concept of early childhood education in Q.S Luqman verses 13-19. The method used in this research is qualitative. Data collection techniques carried out by researchers used observation and interviews. Based on qualitative research methods, all facts, both written and verbal, from primary and secondary data sources are described as they are and then studied to be reduced as concisely as possible to answer the problem. In this research, it was found that Q.S Luqman verse 13 explains about aqidah education for young children which includes teachings about monotheism, namely the belief in the oneness of Allah and the prohibition on associating partners with Him, whereas in QS. Luqman in verses 14-15 explains to young children the morals of being filial to parents. Then Q.S Luqman verse 16 is about matters of education that saves with worship and pious deeds and is emphasized in Q.S Luqman verse 17 that seeking knowledge is something that must be prioritized in carrying out worship, so that you can have akhlahkul Karima and not have akhlah mazuma as explained in Q.S Luqman verses 18-19.